Pengaruh Media sosial Terhadap Gaya Hidup Remaja di Desa Raanan Baru Kecamatan Motoling Barat Kabupaten Minahasa Selatan - Tewal, Aditya Yusak; Mewengkang, Norma N.; Londa, J. W. (ACTA DIURNA KOMUNIKASI, 2018)
In the life of Indonesian society, especially among teenagers, social media seems to have been opium, there is no day without opening social media, even almost 24 hours they are not separated from their smartphones to look around or look for current trendy information. The biggest social media that is often used by teenagers is the Facebook application. But now researchers find some of the antagonisms that occur in teenagers in the new rural area aged 12-21, many of which are often found to be teenagers in the village of New Raanan today, demanding their parents to buy electronic items such as the latest smartphones so they can surf with free and free in cyberspace and also seeing information about their daily lifestyle. Frank Biocca in Littlejohn (1999: 337) for social media variables. (method used). (research result). Peter and Olson (2000: 142) For lifestyle variables. Using a Quantitative approach with a population of 222 people and a sample of 50 people being withdrawn.